Modified Bridgeless Buck Rectifier for LED Applications - C. Pearline Kamalini; M. V. Suganya Devi (Journal of Power Electronics and Devices, 2020)
A great bridgeless buck rectifier for power factor control with a single inductor is planned which extensively builds the proficiency by decreasing the quantity of directing semiconductor segments. The low usage of the attractive segment in the customary bridgeless buck rectifier builds execution. The proposed rectifier’s proficiency is additionally improved by disposing of information connect diodes. Likewise, the rectifier duplicates its yield voltage which broadens utilize capable energy of the mass capacitor after an exit the line voltage. The reenactment of open circle controlled bridgeless buck PFC rectifier with a single inductor and altered converter is acted in MATLAB programming thus its activity is confirmed. The prototype circuit is designed to produce a 12V output voltage suitable for LED applications.